Success in Difficult Environments : A Portfolio Analysis of Fragile and Conflict-Affected States - Ralston, Laura (World Bank Group, Washington, DC, 2014)
The World Bank Group has identified support to fragile and conflict-affected states as a strategic priority. This paper provides a systematic portfolio review of the International Development Association-funded projects in fragile and conflict-affected states during 2001 to 2013 and a detailed empirical analysis of the correlations between project and country-level characteristics with project outcome ratings. The portfolio review identifies a decline in the proportional amount of resources directed to fragile and conflict-affected states and a decline in the number of internationally recruited staff based in these countries. The empirical analysis finds no statistical difference in whether projects obtain at least a moderately satisfactory outcome rating between countries that are fragile and conflict-affected states and those that are not. Examination of the distribution of project outcome ratings indicates that projects in fragile and conflict-affected states obtain slightly lower ratings conditional on being unsatisfactory or satisfactory. Detailed cross-section regression analysis finds that indicators of project complexity, such as supervision costs, staff time, preparation time, and financing, are correlated with lower outcome ratings. Project leader characteristics are correlated with project outcome ratings, but to a lesser degree in fragile and conflict-affected states, potentially indicating that it is more difficult for project leaders to influence project outcomes in these environments. Last, a new approach to control for unobservable project characteristics, such as inherent complexity or ambition, shows preliminary evidence that changes in the project leader and increases in the supervision budget are correlated with improvements in project performance.